SINTUVU AND THE MADIKA SYSTEM OF THE KAILI TRIBE AS A MODEL OF LOCAL WISDOM IN FORMULATING ASYMMETRICAL DECENTRALIZATION POLICIES IN CENTRAL SULAWESI - Randy Atma R. Massi; Wahyuni; Adinda Octaviana; Fira Farisda (Program Studi Perbandingan Mazhab, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2025)
In the context of asymmetric decentralization in Indonesia, integrating local wisdom into constitutional policy formulation is increasingly crucial, particularly in regions with distinctive cultural governance systems. This article examines how the Sintuvu principle and Madika system of the Kaili tribe in Central Sulawesi can serve as a normative and strategic model in formulating asymmetric decentralization policies. Using a normative-legal approach combined with socio-legal analysis, this study demonstrates that the Sintuvu tradition (collective cooperation) and the Madika governmental structure constitute a contextual governance system that aligns with principles of responsive law and legal pluralism. The study analyzes the Pali customary law, the Libu nu Maradika deliberative council, and Givu sanction mechanisms as concrete manifestations of local constitutional values. This research argues that asymmetric decentralization in Central Sulawesi should not merely adopt a formalistic approach but must integrate Kaili traditional governance values as a foundation for inclusive, contextual, and culturally-rooted policies. The article recommends a specific policy formulation model based on the Sintuvu principle as the philosophical foundation for regional governance that honors local constitutional identity.